Prediction of hemorrhagic complications during treatment of children with malignant diseases - V. V. Dmitriev; I. A. Dunaev (Онкогематология)
Achievement of platelet diagnostic threshold less than 28.0 × 109/l and prothrombin activity less than 40 % with system inflammatory response (SIRS) were considered as high risk for spontaneous bleeding complication development within the next day in cancer patients. If platelets count is more than 28.5 × 109/l in a combination to prothrombin activity ≥ 40 % and absence of SIRS, it is possible to say that coagulations changes cannot be the independent cause of bleeding and does not require correction of coagulation parameters.